Answer:
the answer to the question is 5
X(x + 3) + x(x - 3) = 2
x^2 + 3x +x^2 - 3x = 2
2x^2 = 2
x^2 = 1
x = +1 and x = -1
answer
x = +1 and x = -1
Answer:
5(9x + 2y + 10)
or
x = 0
y = -5
Step-by-step explanation:
If you are just factoring this, you will factor a 5 out from everything.
5(9x + 2y + 10)
or if you are trying to solve just isolate one of the variables and then substitute it into the original equation
45x + 10y = 50
10y = 50 - 45x
y = 5 - 4.5x
45x + 10(5-4.5x) + 50
45x + 50 - 45x + 50
x=0
45(0) + 10y + 50
0 + 10y + 50
10y + 50
10y = -50
y = -5
and it would be x = 0 and y = -5